Changing Tracks: Human Capital Investment after Loss of Ability - Anders Humlum; Jakob R. Munch; Pernille Plato (Institute of Labor Economics (IZA), 2023)
We provide the first evidence on how workers invest in human capital after losing ability. Using quasi-random work accidents in Danish administrative data, we find that workers enroll in bachelor's programs after physical injuries, pursuing degrees that build on their work experiences and provide pathways to cognitive occupations. Exploiting differences in eligibility driven by prior vocational training, we find that higher education moves injured workers from disability benefits to full-time employment. Reskilled workers earn 25% more than before their injuries and do not end up on antidepressants. Without higher education, by contrast, these workers end up entirely on disability benefits and often resort to taking antidepressants. Reskilling subsidies for injured workers pay for themselves four times over, and current rates of reskilling are substantially below the social optimum, especially for middle-aged workers.
Keywords: I26; J24; J62; 330; workplace injury; human capital investment; employment; disability insurance